The Development of Modern Arabic in Syntactic and Semantic Perspectives in Alarabiya Magazine - Rosi, Khoirur; Muhammad Thohir (IAIN Madura, 2023)
The purpose of this study is to investigate the modern Arabic language used by Alarabiya online. The focus of this research is on the analysis of the development of meaning and language structure, with the object of research being the online magazine Alarabiya. This study employs lexical, grammatical, and contextual analysis of meaning, as well as syntactic research by analyzing phrases, clauses, and verbs. The theory used in this research is al-Nazhariyyah al-Siyaqiyyah or contextual theory developed by J.R Firth. The research method used is a literature review with two approaches, namely sociolinguistics and lexical statistics. The primary data source in this research is the online magazine Alarabiya. The results of this research indicate that the modern Arabic language used by Alarabiya magazine has undergone many developments in meaning and structure, and has been influenced by the development of science and technology in various fields such as politics, economy, science, and technology.